"Nascer em berço de ouro": os quartos infantis como instância de socialização de crianças pertencentes a estratos sociais favorecidos - Cibele Noronha de Carvalho (2018)
This research uses notions of material culture and interprets the spaces and the system of objects that compose what has been called “bedroom culture”, an outcome of the processes of individualization, specialization of spaces, and recognition of children’s right to privacy. The research followed two phases. In the first phase we analyzed the decoration market through: (a) secondary data from a market research; (b) content analysis of a child-care website; (c) interviews with salespeople from children’s furniture stores. During the second phase we visited houses, interviewed parents, and recorded a video in which the child presented his/her bedroom. The conclusions pointed to a constant recurrence, in the market discourse, of the image of a personalized, original, “far from traditional” bedroom. Instead of following a determined style, each consumer is invited to create their own style. In the bedrooms visited we identified objects that point to an educational ideal of autonomy, so as the children can create and tell their own story, expressing their personality in a personal space. The home visits also pointed the bedroom as a space created by the family and subject to social imperatives. We found objects that are used as a support to remember past generation; objects that are a product and produce a cosmopolitan ethos; as well as objects that turn the bedroom into a school annex, boosting the transmission of families’ cultural capital. Finally, the analysis of bedroom by gender showed how primary socialization happens in gendered spaces.